Randomised trial of personalised computer based information for cancer patients. Issue 7219 (6th November 1999) - Jones, Ray; Pearson, Janne; McGregor, Sandra; Cawsey, Alison J; Barrett, Ann; Craig, Neil; Atkinson, Jacqueline M; Gilmour, W Harper; McEwen, Jim
Abstract: Objective: To compare the use and effect of a computer based information system for cancer patients that is personalised using each patient's medical record with a system providing only general information and with information provided in booklets. Design: Randomised trial with three groups. Data collected at start of radiotherapy, one week later (when information provided), three weeks later, and three months later. Participants: 525 patients started radical radiotherapy; 438 completed follow up. Interventions: Two groups were offered information via computer (personalised or general information, or both) with open access to computer thereafter; the third group was offered a selection of information booklets. Outcomes: Patients' views and preferences, use of computer and information, and psychological status; doctors' perceptions; cost of interventions. Results: More patients offered the personalised information said that they had learnt something new, thought the information was relevant, used the computer again, and showed their computer printouts to others. There were no major differences in doctors' perceptions of patients. More of the general computer group were anxious at three months. With an electronic patient record system, in the long run the personalised information system would cost no more than the general system. Full access to booklets cost twice as much as the general system. Conclusions: Patients preferred computer systems that provided information from their medical records to systems that just provided general information. This has implications for the design and implementation of electronic patient record systems and reliance on general sources of patient information.